2021
DOI: 10.30603/al.v7i2.2176
|View full text |Cite
|
Sign up to set email alerts
|

Realia-Mediated Instruction: An Effective Tool for Improving Young Learners' Vocabulary Skills

Abstract: A foreign language teacher often employs realia to strengthen pupils' association between words and objects. The current study investigates real-life activities that improve vocabulary learning in the English language and the impact of realia on improving students' vocabulary learning performance. It was an experimental study with only post-test design. Forty students participated in the study. The data were collected and analyzed statistically. The results revealed that vital activities used for vocabulary de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Students' vocabulary breadth was evaluated using the Peabody Picture Vocabulary Test Revised (PPVT-R) in two forms: the L form (pretest) and the M form (posttest). The results supported the information given by [12], showing that ELLs and EO speakers had significantly different vocabulary levels. Moreover, the research showed that this disparity is constant all year round.…”
Section: Restricted Lexicon Of English Language Learners (Ells)supporting
confidence: 85%
See 1 more Smart Citation
“…Students' vocabulary breadth was evaluated using the Peabody Picture Vocabulary Test Revised (PPVT-R) in two forms: the L form (pretest) and the M form (posttest). The results supported the information given by [12], showing that ELLs and EO speakers had significantly different vocabulary levels. Moreover, the research showed that this disparity is constant all year round.…”
Section: Restricted Lexicon Of English Language Learners (Ells)supporting
confidence: 85%
“…According to research that shows words are best learned in situations with a lot of meaning, the words chosen for the vocabulary list came from short, interesting readings. A small group of vocabulary words were taught every week (12). These were words that students at this level would likely see again and again in different types of books.…”
Section: Effective Teaching Of Vocabularymentioning
confidence: 99%
“…Reading instruction in Junior High School receives a high level of attention, as seen by the English material offered in text-based genres, where the majority of English material is presented in various types of texts (Bhatti et al, 2021). Students are expected to enhance their language skills through adequate textual comprehension by presenting texts.…”
mentioning
confidence: 99%